Ҳисоб кунед:
$$25.\quad 1,7 : \frac{(4,5 \cdot 1\frac{2}{3} + 3,75) \cdot \frac{7}{135}}{\frac{5}{9}} - (0,5 + \frac{1}{3} - \frac{5}{12}).$$
Ҳал:
\(25. 1,7 : \frac{(4,5 \cdot 1\frac{2}{3} + 3,75) \cdot \frac{7}{135}}{\frac{5}{9}} - (0,5 + \frac{1}{3} - \frac{5}{12}) = 1\frac{17}{84}.\)
\(
1) 4,5 \cdot 1\frac{2}{3} = 4,5 \cdot \frac{5}{3} = 1,5 \cdot \frac{5}{1} = 7,5;
\)
\(
2) 7,5 + 3,75 = 11,25 = 11\frac{25}{100} = 11\frac{1}{4};
\)
\(
3) 11\frac{1}{4} \cdot \frac{7}{135} = \frac{45}{4} \cdot \frac{7}{135} = \frac{45 \cdot 7}{4 \cdot 135} = \frac{1 \cdot 7}{4 \cdot 3} = \frac{7}{12};
\)
\(
4) \frac{7}{12} : \frac{5}{9} = \frac{7}{12} \cdot \frac{9}{5} = \frac{7 \cdot 9}{12 \cdot 5} = \frac{7 \cdot 3}{4 \cdot 5} = \frac{21}{20} = 1\frac{1}{20};
\)
\(
5) 1,7 : 1\frac{1}{20} = 1\frac{7}{10} : \frac{21}{20} = \frac{17}{10} \cdot \frac{20}{21} = \frac{17 \cdot 20}{10 \cdot 21} = \frac{17 \cdot 2}{1 \cdot 21} = \frac{34}{21} = 1\frac{13}{21};
\)
\(
6) 0,5 + \frac{1}{3} = \frac{1}{2} + \frac{1}{3} = \frac{3}{6} + \frac{2}{6} = \frac{5}{6};
\)
\(
7) \frac{5}{6} - \frac{5}{12} = \frac{10}{12} - \frac{5}{12} = \frac{5}{12};
\)
\(
8) 1\frac{13}{21} - \frac{5}{12} = 1\frac{52}{84} - \frac{35}{84} = 1\frac{17}{84}.
\)
Ҷавоб: \(1\frac{17}{84}\).
Ҳисоб кунед: \(1,7 : \frac{(4,5 \cdot 1\frac{2}{3} + 3,75) \cdot \frac{7}{135}}{\frac{5}{9}} - (0,5 + \frac{1}{3} - \frac{5}{12})\)
- Информация о материале
- Автор: Раҳматҷон Ҳакимов
- Категория: Математикаи элементарӣ
- Просмотров: 574
- Таҳқиқи функсияи \(y = \frac{x^3-1}{4x^2}\)
- Таҳқиқи функсияи \(y = \ln{\frac{x+1}{x+2}}\)
- Таҳқиқи функсияи \(y = \frac{e^x}{x}\)
- Таҳқиқи функсияи \(y = -\frac{1}{4}(x^3-3x^2+4)\)
- Соҳаи муайянии функсияи \(y = \frac{x^2}{1+x}\)
- Соҳаи муайянии функсияи \(y = \sqrt{\cos x^2}\)
- Ҳисоб карда шавад: \(\lim\limits_{n \rightarrow \infty}\left(\frac{1}{n^2} + \frac{2}{n^2} + ... + \frac{n-1}{n^2} \right)\)
- Соҳаи муайянии функсияи \(y = \sqrt{\sin\left(\sqrt{x}\right)}\)
- Ҳисоб карда шавад: \(\lim\limits_{n \rightarrow \infty}\frac{1 + a + a^2 + ... + a^n}{1 + b + b^2 + ... + b^n}\)
- Соҳаи муайянии функсияи \(y = \log(x+2) + \log(x-2)\)